2006
DOI: 10.1007/s00059-006-2941-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Suspected (Peri-)Myocarditis and Inflammatory Dilated Cardiomyopathy

Abstract: Inflammatory cardiomyopathy and myocarditis are considered acquired forms of dilated cardiomyopathy. Whereas consensus documents on the diagnosis of myocarditis and perimyocarditis do exist, guidelines on the specific treatment have been established only for the management of pericardial diseases, which at least partly can be applied in analogy to myocarditis. Presently, feasible clinical pathways are available, which can lead to a correct diagnosis and specific treatment. This is illustrated with two cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
16
0
8
Order By: Relevance
“…A small pericardial effusion may indicate a contribution of cardiac inflammation or perimyocarditis to heart failure in diabetic patients. Epicardial fat may be associated with overweight in diabetic patients and may indicate also cardiovascular risk tes with autoimmune features affecting the heart [50]. This inflammation and a possible accompanying or causative viral infection demonstrated by polymerase chain reaction (PCR) in the myocardial tissue will have an impact on the treatment algorithm beyond insulin or oral antidiabetic treatment [48,50].…”
Section: Role Of Endomyocardial Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…A small pericardial effusion may indicate a contribution of cardiac inflammation or perimyocarditis to heart failure in diabetic patients. Epicardial fat may be associated with overweight in diabetic patients and may indicate also cardiovascular risk tes with autoimmune features affecting the heart [50]. This inflammation and a possible accompanying or causative viral infection demonstrated by polymerase chain reaction (PCR) in the myocardial tissue will have an impact on the treatment algorithm beyond insulin or oral antidiabetic treatment [48,50].…”
Section: Role Of Endomyocardial Biopsymentioning
confidence: 99%
“…Bound IgG in rhodamine staining can be found in diabetic cardiomyopathy, but also in inflammatory autoreactive cardiomyopathy (c) together with circulating antisarcolemmal, antiendothelial and anticollagen antibodies, which can be demonstrated by a double sandwich technique in the same biopsy (d) a concomitant virus infection is possible and should be taken into consideration for further specific treatment either with i.v. immunoglobulins or interferon [48,49,50]. Of note, LGE or demonstration of edema by cardiac MRI as well as a combination of biomarkers of heart failure (BNP, NTpro BNP) and necrosis (troponin I or T) can be found when inflammatory or viral heart disease is found in patients with diabetes and impaired function.…”
Section: Role Of Endomyocardial Biopsymentioning
confidence: 99%
“…More recent studies have used immunocytochemical techniques to detect myocardial inflammation in patients with DCM. These have shown that up to 64% of patients have an inflammatory cardiomyopathy and 67% inflammatory endothelial activation [33][34][35]. This inflammation is associated with increased expression of HLA class II histocompatibility antigens and cell adhesion molecules [33].…”
Section: Nonfamilial/nongenetic Dcmmentioning
confidence: 99%
“…It may also apply to the quantitative definition of inflammatory cardiomyopathy by the World Heart Federation's (WHF) Task Forces in 2000 [2,3] or the first classification of the American Heart Association (AHA) in 2006 [4] and the (counter) position statement of the Working Group on Myocardial and Pericardial Diseases of the European Society of Cardiology (ESC) [5,6]. It is true for recent AHA and ESC guidelines on heart failure (see also issue 9/2006 of Herz) or those on the management of pericardial disease by the ESC Task Force 2005 [7], the Japanese approach to cardiomyopathies (Matsumori in this issue [8]) or recommendations in Herz in 2006 for the management of inflammatory cardiomyopathy [9].…”
Section: Bernhard Maischmentioning
confidence: 99%
“…An optimal sequence of biomarkers to be followed to come to an etiologic diagnosis has been suggested. A similar clinical pathway has recently been suggested for different forms of myocarditis [9] and pericardial effusion [7].…”
Section: Bernhard Maischmentioning
confidence: 99%